Assessment and ICP-MS Determination of Toxic Metal Content (Cd, Cr, Ni, and Pb) in Turkish Chicken Meat for Use as Bioindicator for Human Health - Karaaslan, Nagihan M.; Yaman, Mehmet (Atomic Spectroscopy Press Ltd, 2018)
The aim of this study was to determine the toxic metal concentrations in chicken meat consumed by the Turkish population and to establish health risk assessment. The concentrations of cadmium (Cd), chromium (Cr), nickel (Ni), and lead (Pb) in chicken meat produced by seven different suppliers were determined using inductively coupled plasma mass spectrometry (ICP-MS). The Cd concentrations in all samples were found to be lower than the maximum allowable concentration (MAC) of 50 mu g kg(-1). Elic Cr and Ni concentrations in all samples were lower than 700 and 450 mu g kg(-1), respectively, with the exception of Cr in the samples from one producer and of Ni from two other producers. The Pb concentrations (max. 413 mu g kg(-1)) in the samples from three producers were found to be higher than the MAC of 100 mu g kg(-1). Although the concentrations of lead in some samples exceed the limits set by the authorities, risk of developing cancer over a human lifetime was found to be not significant (between 3 to 16 per 1,000,000 persons).
Keywords: Trace-Elements; Yogurt Samples; Copper; Lead; Chromium; Cadmium; Nickel; Risk; Zinc; Iron